Molecular Dynamics Simulations of Ethyl-4-[(α-L-rhamnosyloxy)-benzyl]carbamate from Moringa oleifera Lam. as a Dipeptidyl Peptidase-4 Inhibitor - I Gusti Ayu Intan Puspita Dewi; Enade Perdana Istyastono (Sanata Dharma University, 2025)
Diabetes mellitus is a global health problem that requires innovative solutions. Ethyl-4-[(α-L-rhamnosyloxy)-benzyl]carbamate (ERBC) compound contained in Moringa oleifera Lam. showed potential as a potent dipeptidyl peptidase-4 (DPP4) inhibitor, with an IC50 value of 0.798 µM. Molecular dynamics simulations indicated that ERBC interacts specifically with the active site of DPP4, providing a mechanistic basis for its inhibitory activity. The research utilized the latest technique developed by previously published plug-ins. The molecular docking simulations were performed 100 times. Then, the poses were clustered to sample the probable poses which were then subjected as the inputs in molecular dynamics simulations. Molecular dynamics simulations have shown that the ERBC compound interacts with the DPP4 protein at two possible poses. PyPLIF HIPPOS analysis demonstrated that ERBC, during its second replication, interacts with Glu205 and Glu206, two key amino acids involved in DPP4 activity.